Analysis of arterial stiffness parameters in breast cancer patients undergoing combination anthracycline-containing chemotherapy - E. G. Medvedeva; E. N. Yushchuk; S. V. Ivanova; D. A. Filonenko; L. G. Zhukova; O. S. Trofimenko (Кардиоваскулярная терапия и профилактика)
Aim. To identify and analyze changes of arterial stiffness (AS) parameters in breast cancer patients undergoing combination anthracycline-containing chemotherapy (ACCT).Material and methods. Fifty women with verified breast cancer aged 46,7±7 years with indications for combined ACCT were assessed for AS (carotid-femoral pulse wave velocity (cfPWV) (m/s); cardio-ankle vascular index (CAVI); cardio-ankle pulse wave velocity (caPWV) (m/s); β-stiffness index, novel Russian Stelari and haStart indices) at 4 visits as follows: before ACCT, after 8-12, 20-24 and 48 weeks from the ACCT start.Results. A reliable decrease in cfPWV was revealed at visit 2 (7,48±1,51, p<0,05) and visit 3 (8,34±1,66, p<0,05) with further significant increase at visit 4 when compared with baseline data. Similar reliable changes were demonstrated for the Stelari index. CAVI decreased at visits 2 and 3 with a reliable difference from the values at visits 1 and 4. No reliable changes in β and haStart stiffness indices were obtained during the follow-up period.Conclusion. In patients with breast cancer who underwent combined ACCT, an increase in cfPWV by 0,95 m/s per year was revealed, which indicates accelerated vascular wall aging and a possible increase in cardiovascular risk in this category of patients.